ISOLATION AND CHARACTERIZATION OF PHB PRODUCING MICRO-ORGANISMS ISOLATED FROM ROOT NODULES OF LEGUMINOUS PLANTS - PRIYA KUMARI,; HARISH KUMAR DHINGRA, (The Bioscan, 2013)
Synthetic plastics are highly resistant to be degraded in the environment and pose a number of serious problems. Therefore, there is an urgent need to have a biodegradable alternative to these synthetic polymers.Rhizobium spp. is able to produce poly hydroxyl butyrate (PHB) which can be used as biodegradable plastic. But the cost of production is very high because of high cost of media ingredients and chemicals used for their extraction from the cell. In the present study of investigation, attempts have been made to isolate and characterize the Rhizobium isolates capable of producing PHB and to analyze the effect of cheap carbon and nitrogen sources on their growth. Rhizobium was isolated from the root nodules collected from various leguminous plants. Biochemical and molecular characterization of PHB producing isolates were carried out.To analyze the effect of cheaper carbon and nitrogen sources on PHB production, different concentration of jaggery and soybean meal was used.Different concentration of jaggery and soybean mealranging from 0.2% to 1% was added in the minimal media. It was found that use of 1% jaggery and 0.2% soybean flour in minimal media proved to be the most effective combination for the maximum growth of biomass and production of PHB.